Implementation of COBIT 5 Framework in IT Management at UNISM Library - Kurniawan, Muhamad; Sabrina, Nabila Khalilah; Maulina, Riska; Sabrila, Trifebi Shina; Latif, Abdul; Lindawati, Ratna (LPPM Universitas Sari Mulia, 2024)
In general, COBIT 5 is a framework that helps to focus on Governance and management which includes 2 main areas, namely Governance and Management. So that this study applies the COBIT 5 framework to a library institution at Sari Mulia University. In this study, we used COBIT 5 domains, namely EDM04 (Ensure Resource Optimization) and DSS02 (Manage Service Requests and Incidents), both of which focused on optimizing resources (IT) as well as managing service requests and incidents. This study uses methods that include qualitative and quantitative approaches by collecting data through interviews and surveys. The results show that the implementation of COBIT 5 can improve the efficiency of IT resource use as well as improve the response to IT service incidents. The average level of IT maturity is at level 3 (Established), although there are some gaps that need to be addressed to reach the optimal level. This research provides important insights for libraries in optimizing IT governance to support better services.